Education and Teaching: a matter of agreement or dispute between the State and the Catholic Church during the Portuguese authoritarian regime? - Santos, Paula Borges (Historia y Memoria de la Educación, 2016)
This paper discusses whether the issues related to education and teaching were the object of understanding or of conflict between the authoritarian State and the Catholic Church in Portugal. The period covered spans the entire dictatorship (1933-1974). An analysis is made of both the status given to religion in public education and in the State structures for youth integration, as well as the treatment given to private confessional education. The paper starts with a brief characterisation of the State-Church relationship model, here referred to as «second separation». The paper then seeks to confirm the framework outlined by focusing on the principal issues taken up by the State and the Catholic Church regarding «mixed matters»: constitutional amendments related to the guiding principles of public education, the placing of crucifixes in schools, religious assistance in State youth organisations, the situation of private education, the creation of the Portuguese Catholic University and regulation of the task of religious and moral education. Certain governance strategies are questioned: the political agenda, policy making and legislating. The paper explores the behaviour of Church agents by looking at their strategies of commitment, their resistance or promotion of religious interests, and their ability to influence policy makers.